Experimental investigation of transpiration cooling for sintered woven wire mesh structures. (December 2015) - Xu, Guoqiang; Liu, Yangpeng; Luo, Xiang; Ma, Jiandong; Li, Haiwang
Highlights: The transpiration cooling for wire mesh structures were investigated experimentally. The empirical equation is not suitable for sintered woven wire mesh structures. The influence of parameters including structure and flow condition was investigated. Abstract: Experiments were conducted to investigate the transpiration cooling performance of the sintered woven wire mesh structures with different porosities at various blowing ratios in this paper. All the test pieces made of stainless steel wires with the same average wire ( d = 0.14 mm) were sintered after woven. In the experiments, the air applied by compressors was used to investigate the transpiration cooling performance of the structures as main flow and coolant. The effects of main flow conditions and porosities of test pieces on the cooling efficiency were investigated. The cooling efficiency of the structure were calculated based on the definition of η = T wa - T w T wa - T c . The surface temperature of test pieces was measured using an infrared camera. The results showed that the main flow conditions have a little influence on the transpiration cooling performance within the range of experimental parameters. At the same time, the averaged surface temperature decreases along the main flow direction and decreases as the increase of the blowing ratio which means that the cooling efficiency increases as the blowing ratio increases. It can be considered that the transpiration cooling efficiency for test piece 55% is higher than the film cooling efficiency and the transpiration cooling efficiencies for test piece 47% and 37% may be higher than the film cooling efficiency at large blowing ratios within the range of experimental parameters in this paper. The experimental results also indicated that the conclusion obtained using porous medium in the pioneer work cannot be used directly to predict the properties of the sintered woven wire mesh structures.